Self-relevance and the activation of attentional networks. Issue 5 (May 2023) - Svensson, Saga; Golubickis, Marius; Johnson, Sam; Falbén, Johanna K; Macrae, C Neil
Recent theoretical accounts maintain that core components of attentional functioning are preferentially tuned to self-relevant information. Evidence in support of this viewpoint is equivocal, however, with research overly reliant on personally significant (i.e., familiar) stimulus inputs (e.g., faces, forenames) and a diverse range of methodologies. Addressing these limitations, here we utilised arbitrary items (i.e., geometric shapes) and administered the Attention Network Test (ANT) to establish the extent to which self-relevance (vs friend-relevance) moderates the three subsystems of attentional functioning—alerting, orienting, and executive control. The results revealed that only executive control was sensitive to the meaning of the stimuli, such that conflict resolution was enhanced following the presentation of self-associated compared with friend-associated shapes (i.e., cues). Probing the origin of this effect, a further computational analysis (i.e., Shrinking Spotlight Diffusion Model analysis) indicated that self-relevance facilitated the narrowing of visual attention. These findings highlight when and how the personal significance of otherwise trivial material modulates attentional processing.